Influence of Humidity State on Dynamic Resilient Modulus of Subgrade Soils: Considering Repeated Wetting-Drying Cycles - Gongfeng Xin; Anshun Zhang; Zijian Wang; Quanjun Shen; Minghao Mu (Advances in Materials Science and Engineering)
The service performance of subgrade depends on the dynamic resilient modulus (MR) of subgrade soils. Meanwhile, due to complicated conditions such as rainfall infiltration, high temperature evaporation, and groundwater level fluctuations, it can be safely said that the humidity state and repeated wetting-drying (WD) cycles affect the MR of subgrade soils. The object of this study is to conduct a series of dynamic triaxial tests after WD cycles to investigate the characteristics of the MR under various factors. The main results are as follows: (i) the MR decreased with the increase of deviator stress and rose with the growth of confining pressure; (ii) the humidification effect caused by the increase in moisture content attenuated the MR; (iii) the accumulation of WD cycles damaged the MR; however the decline rate was gradually retarded until it was stable with WD cycles 5 times; (iv) the satisfactory prediction model for the MR of subgrade soils considering WD cycles was proposed and verified. It is expected that the findings can provide valuable contributions for road engineering.